2002
DOI: 10.1002/immu.200390017
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of DC‐SIGN+IL‐12+IL‐18+ and CD83+IL‐12IL‐18 dendritic cell populations in the colonic mucosa of patients with Crohn's disease

Abstract: Dentritic cells (DC) as antigen-presenting cells are most likely responsible for regulation of abnormal T cell activation in Crohn's disease (CD), a chronic inflammatory bowel disease. We have analyzed the expression of activation and maturation markers on DC in the colon mucosa from patients with CD compared with normal colon, using immunohistochemical techniques. We found two distinct populations of DC present in CD patients: a DC-specific ICAM-3 grabbing non-integrin (DC-SIGN) + population that was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 34 publications
4
99
1
Order By: Relevance
“…In addition, tumors use a variety of mechanisms to evade detection and elimination by the immune system (19,23). Maturation of DCs is crucial for their ability to induce adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tumors use a variety of mechanisms to evade detection and elimination by the immune system (19,23). Maturation of DCs is crucial for their ability to induce adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…8A), suggesting that the increased expression of DC-SIGN ligands on colorectal cancer cells, in addition to the altered glycosylation that results in increased levels of Le a and Le b glycans on colorectal cancer cells, may promote interactions with DC-SIGN. It has been reported that DC-SIGN-positive cells are detected not only within the mucosa of normal colon tissue but also within cancer colon tissue (14,19). Next, to determine whether DC-SIGN-positive cells may interact with primary colorectal cancer cells in situ, we analyzed the interaction of endogenous DC-SIGN with Le a glycan in cancer colon tissue.…”
Section: Dc-sign Mediates the Interaction Of Dcs To Primary Colorectamentioning
confidence: 99%
“…In addition the presence of CD83 + and DC -SIGN + DCs was described [19] . Human and mouse mucosal DCs are assumed to be less responsive to microbial-derived TLR-lig ands compared to spleen or blood born DCs [17] Despite the functional subspecifications of DCs, DCs are characterized by a remarkable plasticity between DCs which is influenced by the local environment, the antigen itself or the activation state of the DC [9,20] .…”
Section: Dcs In the Large Intestinementioning
confidence: 99%
“…In inflamed tissues DCs are matured and increased in 5142 ISSN 1007-9327 CN 14-1219/R World J Gastroenterol Volume 14 Number 33 numbers. The CD83 -CD80 + DCSIGN + DC subsets produce the cytokine IL-12 and IL-18, which promote TH1 development [19] . Also, in the peripheral blood and in the lamina propria of patients with CD or UC the numbers of CD86 + CD40 + DCs are increased.…”
Section: Dcs In Ibdmentioning
confidence: 99%
“…This is likely due to difficulties in obtaining large enough samples from the relevant tissues to identify these scarce cells. However, studies using immunohistochemistry have been performed on biopsies from the colon of normal individuals and Crohn's Disease patients and showed the presence of different subsets of phagocytes in human colon [27][28][29][30]. Information obtained from immunohistochemical stainings is invaluable since they also show the location of the cells within the tissue.…”
Section: Phagocyte Subsets In the Human Intestinementioning
confidence: 99%